2022
DOI: 10.3389/fgene.2022.823443
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis-Related Risk Signature Exhibits Distinct Prognostic, Immune, and Therapeutic Landscapes in Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a common abdominal cancer. The existing therapeutic approaches often fail to achieve satisfactory results. Pyroptosis, an inflammatory form of programmed cell death, provides new ideas for anticancer treatment. However, the roles of pyroptosis-related (PR) genes (PRGs) in HCC remain elusive.Methods: Differentially expressed genes (DEGs) (n = 22) were screened out using TCGA and GTEx databases. A novel PR risk signature was constructed through Lasso regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In the end, we demonstrated that the risk score could be employed as a standalone indicator judging the prognosis of BLCA, and the HR value of risk score was much higher than HR value of age and tumor stage, which indicated that it was more meaningful to evaluate the BLCA patients’ prognosis by risk score than by age and tumor stage. Similar results have been reported in other cancer studies [ 54 , 55 ]. A nomogram is recognized as a convenient method to speculate the survival probability of patients [ 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the end, we demonstrated that the risk score could be employed as a standalone indicator judging the prognosis of BLCA, and the HR value of risk score was much higher than HR value of age and tumor stage, which indicated that it was more meaningful to evaluate the BLCA patients’ prognosis by risk score than by age and tumor stage. Similar results have been reported in other cancer studies [ 54 , 55 ]. A nomogram is recognized as a convenient method to speculate the survival probability of patients [ 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, WNK1 triggers the progression and invasion of HCC cell lines and xenograft tumors via its interaction with lncRNAs in the tumor microenvironment 64 . On the other hand, inhibition of WNK1 diminished its stimulative capabilities on proliferation, invasion, and migration in HCC cells, which is suggested to be mediated via activating AMPK and autophagy 32,65 . Nonetheless, the functional significance of WNK1 in lenvatinib resistance in HCC was neither reported nor anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…64 On the other hand, inhibition of WNK1 diminished its stimulative capabilities on proliferation, invasion, and migration in HCC cells, which is suggested to be mediated via activating AMPK and autophagy. 32,65 Nonetheless, the functional significance of WNK1 in lenvatinib resistance in HCC was neither reported nor anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…HCC cells with different drug sensitivity were used for in vitro validation. We compared the C-index values of several latest prediction signatures in HCC with ours ( Lin et al, 2022 ; Miao et al, 2022 ; Ye et al, 2022 ; Zhao et al, 2022 ; Zhou et al, 2022 ) ( Supplementary Figure S2 ). Genes in the prediction signature are listed in Supplementary File S4 .…”
Section: Discussionmentioning
confidence: 99%